Migrações e políticas migratórias na globalização: os desafios político-sociais do estado - Souza, Edu Morais de (2013)
As a constituent part of the current process of globalization, international migration flows assumed original features resulting from reciprocal relations with this step, also known as late/multinational capitalism. The sociopolitical, economic and cultural implications of this process have led states to reorient their role in border control. However, the complexity of the systems of regulation and barriers to human mobility nowadays have generated a redefinition of the relationship of autonomy/subordination of states against other influential actors in the elaboration of migration policies, setting up a major political field. In this sense, the main objective of this work is to examine the issues surrounding the role of the developed states in the development/implementation of migration policies in relation to the demands of different local and global actors. This analysis is built around contemporary social theory, based on the studies of Saskia Sassen, Douglas Massey and Gary Freeman.